(untitled) (Pedagogical Horizons, 2024)
Teachers are seen as key players in the process of democracy education (Schneider & Gerold, 2018, p.6). In light of this, the present replication study "Democracy Education at Upper Austrian Schools" by the University College of Teacher Education of the Diocese of Linz examines the current state of democracy education from the perspective of Upper Austrian teachers. The assessment of the teaching culture can generally be assessed as conducive to democracy, although improvements could be initiated in the teaching of democratic skills, the use of various democracy education formats and the treatment of topics that promote democracy. The results of the study indicate that the competence profile and self-efficacy experiences of teachers are decisive for how strongly democracy education is anchored in schools. It is emphasized that time restrictions or school bureaucratic requirements do not necessarily limit teachers’ scope for action in this area. Furthermore, it is argued that strengthening democracy education in schools requires teachers to receive more training and qualifications. Not only university teacher training institutions play a role here, but also further education and training courses at teacher training colleges and civil society actors such as NGOs. The development of new qualification programs should therefore take place in a broad social context in order to give impetus to the current discussions on democracy education and to support teachers in their central role as mediators of democratic values and skills.